207k views
3 votes
The substitution method solve 6x-y=3 4x+3y=1

User Inderjit
by
5.1k points

2 Answers

2 votes
y= - 3 + 6x
4x+3y=1
4x+3(-3 + 6x) = 1
4x-9+18x-1=0
22x= 0
22x= -8
x = -8/22 = -4/11
User David Moore
by
5.1k points
6 votes

Answer:


( (5)/(11) \:</strong><strong>,</strong><strong> - (3)/(11) )

Explanation:

6x - y = 3

4x + 3y = 1

Solve the equation for y

y = -3 + 6x

4x + 3y = 1

Substitute the given value of y into the equation

4x + 3y = 1

plug the value


4x + 3( - 3 + 6x) = 1

Distribute 3 through the parentheses


4x - 9 + 18x = 1

Collect like terms


22x - 9 = 1

Move constant to R.H.S and change its sign


22x = 1 + 9

Calculate the sum


22x = 10

Divide both sides of the equation by 22


(22x)/(22) = (10)/(22)

Calculate


x = (5)/(11)

Now, substitute the given value of x into the equation

y = -3 + 6x


y = - 3 + 6 * (5)/(11)

Solve the equation for y


y = - (3)/(11)

The possible solution of the system is the ordered pair ( x , y )


(x </strong><strong>,</strong><strong>\: y) = ( (5)/(11) </strong><strong>,</strong><strong>\: - (3)/(11) )

-----------------------------------------------------------

Check if the given ordered pair is the solution of the system of equations


6 * (5)/(11) - ( - (3)/(11) ) = 3


4 * (5)/(11 ) + 3 * ( - (3)/(11) ) = 1

Simplify the equalities


3 = 3


1 = 1

Since all of the equalities are true , the ordered pair is the solution of the system


( \: x </strong><strong>,</strong><strong>\: y \: ) = ( (5)/(11) \:</strong><strong>,</strong><strong> - (3)/(11) )

Hope this helps..

Best regards!!

User Tal Darom
by
5.3k points